Finding mobility in place attachment research: lessons for managed retreat - Willcocks-Musselman, Robin; Baird, Julia; Foster, Karen; Woodhall-Melnik, Julia; Sherren, Kate (Frontiers in Climate, 2025)
Climate change will affect many global landscapes in the future, requiring millions of people to move away from areas at risk from flooding, erosion, drought and extreme temperatures. The term managed retreat is increasingly used in the Global North to refer to the movement of people and infrastructure away from climate risks. Managed retreat, however, has proven to be one of the most difficult climate adaptation options to undertake because of the complex economic, social-cultural and psychological factors that shape individual and community responses to the relocation process. Among these factors, place attachment is expected to shape the possibilities for managed retreat because relocation disrupts the bonds and identities that individuals and communities have invested in place. Research at the intersection of place attachment and managed retreat is limited, partially because these are complicated constructs, each with confusing terminologies. By viewing the concept of managed retreat as a form of mobility-based climate adaptation, this paper attempts to gain insights from other mobility-related fields. We find that place attachment and mobility research has contributed to the development of a more complex and dynamic view of place attachment: such research has explored the role of place attachment as either constraining or prompting decisions to relocate, and started to explore how the place attachment process responds to disruptions and influences recovery from relocation. Beyond informing managed retreat scholars and practitioners, this research synthesis identifies several areas that need more attention. These needs include more qualitative research to better understand the dualistic role of place attachments in decisions to relocate, more longitudinal research about relocation experiences to fully comprehend the place attachment process during and after relocation, and increased exploration of whether place attachments can help provide stability and continuity during relocation.